2017
DOI: 10.7554/elife.26910
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus recruits host protein kinase C to control assembly and activity of its replication machinery

Abstract: Influenza virus expresses transcripts early in infection and transitions towards genome replication at later time points. This process requires de novo assembly of the viral replication machinery, large ribonucleoprotein complexes (RNPs) composed of the viral polymerase, genomic RNA and oligomeric nucleoprotein (NP). Despite the central role of RNPs during infection, the factors dictating where and when they assemble are poorly understood. Here we demonstrate that human protein kinase C (PKC) family members re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 73 publications
2
66
0
Order By: Relevance
“…Like other viral pathogens, IAV lacks the machinery required for lipid biosynthesis. As it hijacks the host cellular machinery for its replication (17,61), newly assembled IAV acquires its envelope from the host membrane, where sphingolipids are key constituents (62). Previous studies have shown that IAV requires lipid rafts and intact sphingolipid biosynthesis for replication and morphogenesis (62)(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Like other viral pathogens, IAV lacks the machinery required for lipid biosynthesis. As it hijacks the host cellular machinery for its replication (17,61), newly assembled IAV acquires its envelope from the host membrane, where sphingolipids are key constituents (62). Previous studies have shown that IAV requires lipid rafts and intact sphingolipid biosynthesis for replication and morphogenesis (62)(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Protein interactions were detected by SDS-PAGE and Coomassie staining. Primer extensions were performed using RNA extracted from cells where RNPs were reconstituted without NP using a micro vRNA template (77 nt derived from NP) (Mondal et al, 2017;Turrell et al, 2013).…”
Section: Viruses and Plasmidsmentioning
confidence: 99%
“…A basic groove separating the head and body domains represents the RNA-binding surface. Phosphorylation and dephosphorylation of NP by cellular kinases and phosphatases affects NP oligomerization and viral replication (Hutchinson et al 2012;Chenavas et al 2013;Mondal et al 2015Mondal et al , 2017Turrell et al 2015). The footprint of NP on vRNA is ∼24 nucleotides (Ortega et al 2000;Hutchinson et al 2012), but it is not known how many nucleotides make direct contact with NP and how the RNA is arranged in vRNPs.…”
Section: Architecture Of Vrnpsmentioning
confidence: 99%